1996
DOI: 10.1007/bf02002904
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study on the atopy preventive effect of maternal avoidance of milk and eggs during pregnancy and lactation

Abstract: While breast feeding should be promoted for children at risk for atopy, mothers can be encouraged to stay on normal diet during pregnancy and the breast feeding period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 14 publications
0
42
0
Order By: Relevance
“…In one non-randomized preference trial, 30 women chose to completely avoid milk and eggs in the last trimester of pregnancy and while breastfeeding exclusively; 33 women also avoided all milk and eggs, but only while breastfeeding; and 41 women chose no dietary restrictions [41]. In this study, six children of mothers in each of the avoidance groups had eczema in the first year of life compared with 5 children in the group where mothers did not follow dietary restrictions.…”
Section: Intervention Studiesmentioning
confidence: 86%
See 2 more Smart Citations
“…In one non-randomized preference trial, 30 women chose to completely avoid milk and eggs in the last trimester of pregnancy and while breastfeeding exclusively; 33 women also avoided all milk and eggs, but only while breastfeeding; and 41 women chose no dietary restrictions [41]. In this study, six children of mothers in each of the avoidance groups had eczema in the first year of life compared with 5 children in the group where mothers did not follow dietary restrictions.…”
Section: Intervention Studiesmentioning
confidence: 86%
“…Solid foods were delayed and the children were followed for eczema and food allergy until 10 years of age. Herman et al [41] enrolled 150 pregnant women into a patient preference trial of avoiding cow's milk and egg during pregnancy and lactation. They followed children until 1 year of age for eczema and sensitization.…”
Section: Intervention Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Subsequent systematic reviews of the literature concluded that the current evidence is inadequate to support any dietary restrictions during pregnancy. [6][7][8][9] The majority of studies on this topic have been conducted in populations selected for allergic propensity, [10][11][12][13][14] rendering inference to the general population challenging. Further, previous studies of the potential impact of maternal diet during pregnancy have examined only the last month or trimester of pregnancy [10][11][12][13][14][15][16][17][18] and analyzed outcomes only in the first year(s) of life.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] The majority of studies on this topic have been conducted in populations selected for allergic propensity, [10][11][12][13][14] rendering inference to the general population challenging. Further, previous studies of the potential impact of maternal diet during pregnancy have examined only the last month or trimester of pregnancy [10][11][12][13][14][15][16][17][18] and analyzed outcomes only in the first year(s) of life. [10][11][12][13][16][17][18] Because many cells thought to be involved in the pathogenesis of allergy and asthma are formed during early pregnancy 19,20 , an examination of exposures during the first and second trimesters could be worthwhile.…”
Section: Introductionmentioning
confidence: 99%